Association of a standardized measure of nasopharyngeal inflammation with Eustachian tube dysfunction questionnaire score. Issue 8 (27th January 2021) - Bergeron, Jeffrey M.; Parsel, Sean M.; Do, Triet M.; Unis, Graham D.; McCoul, Edward D.
Abstract : Background: Standardized diagnostic criteria for Eustachian tube (ET) dysfunction (ETD) have not been established. The purpose of this study was to characterize the relationship between ET inflammation and ETD symptoms and to determine the diagnostic performance of a quantitative score. Methods: Patients were enrolled in a rhinology clinic between October 2018 and June 2019. Patients underwent nasal endoscopy and completed the 7‐item Eustachian Tube Dysfunction Questionnaire (ETDQ‐7). Nasopharyngeal inflammation identified on endoscopy was quantified using the Endoscopic Evaluation of the Eustachian Tube (3ET) score. Tympanometry was performed as indicated. Comorbid conditions were assigned during the patient encounter. Results: A total of 414 patients were included in the study. Patients with clinically significant ETD symptoms (ETDQ‐7 ≥2.1) had higher 3ET scores than those without symptoms. A 1‐point increase in 3ET score was associated with a 1.7‐fold increase in odds of clinically significant ETD symptoms (adjusted OR [aOR], 1.72; 95% CI, 1.46 to 2.05). The 3ET scores were correlated with ETDQ‐7 scores ( ρ  = 0.54) and 22‐item Sino‐Nasal Outcome Test (SNOT‐22) scores ( ρ  = 0.52). 3ET scores were not associated with tympanometric peak pressures. Patients with ETD symptoms were more likely to have laryngopharyngeal reflux (aOR, 2.71; 95% CI, 1.24 to 6.18). A 3ET score of 4 predicted symptomatic state in 80% of cases with a specificity of 97.8% and positive predictive value of 96.6%. Conclusion: Inflammatory findings at the nasopharyngeal ET orifice are associated with clinically significant ETD symptoms. The 3ET score is specific for a symptomatic state and has potential clinical utility in the evaluation of suspected ETD. ©2021 ARSAAOA, LLC.